2000
DOI: 10.3109/10731190009118576
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Evaluation of the Location, the Functional Integrity and the Oxygen Supply of Implants:19F Nuclear Magnetic Resonance Imaging of Perfluorocarbon-Loaded BA2+-Alginate Beads

Abstract: 19F nuclear magnetic resonance imaging (MRI) can be used as a non-invasive tool to simultaneously determine the location, the integrity and the oxygen supply of Ba2+-alginate implants. This requires that the beads (implants) are pre-loaded with the perfluorocarbon compound F-44E. Implantation of solid 19F-labelled beads into the peritoneum, below the kidney capsule or into the muscle of Wistar WU rats demonstrated that these beads could be detected by 19F-MRI for up to 18 months after implantation. This indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…The most likely explanation for these findings is that the microcapsules float freely in the peritoneal cavity without any vascularization. The supply of the encapsulated islets with nutrients and oxygen is, therefore, rather limited as evidenced by 19 F nuclear magnetic resonance imaging (29). Therefore, compromised nutrient and oxygen supply to the islets might lead to mass loss (8) and, in turn, a reduction in insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation for these findings is that the microcapsules float freely in the peritoneal cavity without any vascularization. The supply of the encapsulated islets with nutrients and oxygen is, therefore, rather limited as evidenced by 19 F nuclear magnetic resonance imaging (29). Therefore, compromised nutrient and oxygen supply to the islets might lead to mass loss (8) and, in turn, a reduction in insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…While noninvasive evaluation of oxygen supply at different implantation sites has been performed using cell-free PFC constructs, 35,36 our work involves the investigation of oxygen levels within functional, cell-containing pancreatic implants. In this study, we demonstrated that in vivo realtime oxygen measurements within a tissue-engineered pancreatic construct, implanted in a diabetic mouse model, can…”
Section: Discussionmentioning
confidence: 99%
“…PFC-loaded alginate beads implanted into the rodent kidney capsule, peritoneal cavity, and quadriceps femoris muscle reveal a hypoxic environment unconducive to islet survival. 38,[42][43][44] Macroencapsulated cell systems, however, are often implanted into the subcutaneous space 2 and these studies, limited to microencapsulation, did not examine the oxygen availability of this site.…”
Section: Introductionmentioning
confidence: 99%